Теория секуляризации в европейском научном дискурсе - Паращевин, М. (Социология: теория, методы, маркетинг, 2006)
The article deals with the content of secularization theory and its existing variants. Different arguments for and against this theory are also analyzed. The author arrives at a conclusion that secularization theory has arisen in the intellectual western world as a logical extension of the progress theory, based mainly on empirical data from Western Europe and North America besides some examples from non-Christian countries. The theory declares a gradual decline both of organized religion and personal religiousness. Existing data contain both validation of its points and reasoned disproof, but latter is also disputable. Thus secularization theory is rather applicable to social reality within definite limitations.